Toward nuclear SPICE – integrating IEC 61508, IEC 60880 and SPICE. Issue 3 (18th February 2013) - Varkoi, Timo; Nevalainen, Risto; Mäkinen, Timo; Biró, Miklós; Messnarz, Richard; Colomo‐Palacios, Ricardo
ABSTRACT International Organization for Standardization/International Electrotechnical Commission 15504 has been applied to several domains, where safety is one main characteristic for software and systems. Nuclear power industry is one of the most challenging domains, because of its extreme safety requirements. Nuclear power domain has also a long tradition in using its own standards, classifications and certification schemes. This article discusses the Nuclear SPICE model and how it combines both SPICE related generic requirements with functional safety and nuclear specific elements. Conformance with standards is not any absolute guarantee for safety. Safety can be achieved only by using several different approaches, which all provide their own evidences and support for qualification and licensing. Copyright © 2013 John Wiley & Sons, Ltd.